Lungs Ultrasound in SARS-Cov-2 Diagnostics: a Prospective Comparative Study of 30 Patients with COVID-19 Pneumonia - Svetlana A. Rachina; Daria A. Strelkova; Flora E. Cabello Montoya; Olga T. Zorya; Ayten F. Safarova; Olga V. Aryutina; Stanislav K. Gruzdev; Vladimir V. Mladov (Ministry of Health of the Russian Federation. National Medical Research Center of Rehabilitation and Balneology, 2023)
INTRODUCTION. Lung ultrasound has been widely used to diagnose bacterial pneumonia, pulmonary congestion in heart failure, pneumo- and hydrothorax, and other pathological conditions. With the onset of the COVID-19 pandemic, the need for various methods of lung imaging has dramatically increased. AIM. To estimate the value of lung ultrasound in the diagnosis and severity assessment of COVID-19. MATERIAL AND METHODS. Patients with a positive PCR test result for SARS-Cov-2 were included and divided into a moderate, severe, or critical severe group. There were 30 patients involved. All the patients underwent clinical assessment, complete blood count, biochemical blood profile, pulse oxymetry, bedside lung ultrasound, and chest CT scan. To evaluate LUS findings thorax into 16 lung regions and each of these areas was quantitatively scored and summed up in total LUS score. A total severity score for chest CT was compared with the total LUS score. RESULT AND DISCUSSION. All patients had positive LUS findings, as well as positive CT findings. Most common lung ultrasound findings were the following: subpleural consolidations (100.0%, 30/30), large consolidations (73.3%, 22/30) and an irregular pleural line (43.3%, 13/30). A higher total lung ultrasound score was seen in patients with a more severe course of illness and a larger number of lung areas affected; they were older and had a significantly higher incidence of comorbidities and lower SpO2. Spearman correlation coefficient revealed a statistically significant correlation between CT chest scan and lung ultrasound - rs=.52, p= 0.003011. CONCLUSION. During the COVID-19 pandemic, lung ultrasound is a great tool for assessing lung tissue in patients with varying severity of the disease. The advantages of the method are accessibility, ease of implementation and the absence of radiation exposure.